(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
From a sedimentological and palaeogeographical point of view, in the eastern margin of the Iberian platform system, Middle Jurassic deposits are represented by a thick pile of carbonates with minor marls interbedded. Different facies, within the Tortosa, Aragonese and Castilian platforms, pertain to two categories: internal platform and external platform facies. A system of extensional faults was the major factor determining the differentiation of several shallow, carbonate, epicontinental platforms. The so-called Iberian Basin was a shallow intracratonic platform system, in which a relatively deep extensional basin (the Catalan Basin) started to be differentiated during the late Bajocian. In the eastern part of this faulted platform system, the occurrence of a listric fault, dipping towards the east, conditioned the development of a late Bajocian differentiated subsident area named the Tortosa Platform. From a palaeobiogeographical point of view, the ammonite fossil assemblages of the Iberian platforms are composed of Sub-Mediterranean taxa. At the eastern margin of the Iberian platform system, the appearance and distribution of shells of ammonoids were taphonomically and ecologically controlled by regional changes of relative sea level. A Sub-Mediterranean zonation can be recognized, although most of the ammonites shells correspond to adult individuals arrived by necroplanktic drift from more open-marine or oceanic areas. The following criteria are relevant in recognizing the maximum deepening episodes in the Iberian platform system: colonization (including ontogenic development) of open-marine taxa, immigration of oceanic taxa and development of endemic species. In terms of Sequence Stratigraphy, the development of expanded, external platform sections in the Tortosa Platform during the Garantiana Biochron (late Bajocian) is noteworthy. During this episode, the Iberian platform system reached the maximum bathymetric values and acted as a biogeographical dispersal area for some taxonomic groups of ammonoids between the Western Tethys and the Proto-Atlantic.